Evaluación de las convulsiones mediante el uso del aceite endocannabinoide en caninos de la parroquia de Cumbayá del distrito metropolitano de Quito. - Velastegui Correa, Anthony Gabriel (2021)
In this investigation named “Evaluation of seizures through the endocannabinoid oil usage in canines from the Cumbaya Parish of the Metropolitan District of Quito” the objective was to assess seizure episodes by observing and recording episodes, defining the frequency and intensity as factors to be determined. The sampled population was 15 canines with the confirmed pathology considering their weight, height, age, CBD concentration need, and dosage. Three groups were classified depending on the required CBD concentration, by doing this, we can identify which of the three concentration is better. As a result, in all cases there was an improvement not only in its intensity but in its frequency, there was a better acceptance of the oil with the concentration of 10% and 15%. Concluding with the socialization of results that were of high impact by the canines’ owners, obtaining a pleasant response when seeing the results, they have committed to respect and continue the treatment, the biochemical and oil were given to each owner.